Psychologiczne konsekwencje (euro)sieroctwa: styl życia rodziny, diagnoza i wsparcie - Brzezińska, Anna Izabela; Matejczuk, Joanna (My University, 2011)
Economic migration, especially to Western Europe, is increasingly the reaction of Poles to the presently occurring political, economic, and social changes. The mass exodus and the resulting family separation are becoming a serious social problem, especially in relation to the issues of the development and education of children and youth left behind – commonly known as Euro-orphans. Psychological consequences of Euromigration are experienced by all family members i.e. parents-spouses, children, grandparents, as well as the immediate surrounding – friends, neighbours, school, and local community. The balance of positive and negative effects of decisions made by the family in the period of political transformation also those concerning the place of living and employment either together or separately depends, to a great extent, on the mode of reaching the decisions and implementing them by the whole family. We pay particular attention to the degree of involvement of all family members in the decision making process concerning migration and to the necessity of preparing the family in advance to make conscious and responsible choices. Family counsellors play an essential role in this field.
Psychological consequences of (Euro)orphanhood: family life style, diagnosis and support
Migracje zarobkowe, szczególnie do krajów Europy Zachodniej, staja się coraz częstsza odpowiedzią Polaków na dokonujące się zmiany polityczne, ekonomiczne i społeczne. Masowe wyjazdy oraz wynikająca z nich rozłąka z rodzina staja się poważnym problemem społecznym, zwłaszcza w odniesieniu do problemów rozwoju i wychowania pozostających w kraju dzieci i młodzie y – zwanych potocznie eurosierotami. Psychologicznymi konsekwencjami eurowyjazdów obarczeni zostają wszyscy członkowie rodziny, tj. rodzice-małżonkowie, dzieci, dziadkowie, a tak e najbliższe otoczenie – przyjaciele, sąsiedzi, szkoła, społeczność lokalna. Bilans pozytywnych i negatywnych konsekwencji decyzji dokonywanych przez rodzinę w czasach transformacji, równie decyzji o wspólnym bądz osobnym miejscu zamieszkania i zatrudnienia, w du ej mierze zależy od sposobu podejmowania i realizowania tych decyzji przez cała rodzinę. Zwracamy szczególna uwagę na stopień zaangażowania wszystkich członków rodziny w proces podejmowania decyzji o migracji oraz na konieczność wcześniejszego przygotowania rodziny do świadomego i odpowiedzialnego dokonywania wyborów. Szczególna rola przypada w tym obszarze doradcom rodzinnym.
Keywords: diagnoza sytuacji rodzinnej; doradca rodzinny; eurosieroctwo; migracja; perspektywa czasowa; styl życia; transformacja społeczna; transformacja ustrojowa; wsparcie społeczne; Euroorphanhood; family counselor; family situation diagnosis; migration; life style; political transformation; social support; social transformation; temporal orientation